ASSESSING LEARNERS IN A MIXED-ABILITY CLASSROOM - Barno Shag’darovna Rahmonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: The mixed-ability classroom students have different levels of English language in the classroom. They differ in their language proficiency from beginners to advanced level learners, with their background knowledge of English.